Anti-adhesion coating for injection mold and preparation method of anti-adhesion coating

By using an anti-adhesive coating containing modified anti-adhesive agent and nano-silica/graphene oxide @PDA on the injection mold, the adhesion problem between the injection mold surface and the product is solved, and excellent anti-adhesive, wear and corrosion resistance are achieved, extending the service life of the mold.

CN119708899AInactive Publication Date: 2025-03-28DONGGUAN JIUJIANG NANO TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411907861.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the rubber product production process, the adhesion problem between the injection mold surface and the product leads to defects on the surface of the product, affecting product quality, reducing the service life of the mold, and damaging the mold surface.

Method used

An anti-adhesion coating for injection molds is adopted, and its components include polytetrafluoroethylene water-based resin, methyl methacrylate, acrylic resin, modified anti-adhesion agent, nanosilica/graphene oxide @PDA and additives, and a coating with excellent anti-adhesion, wear and corrosion resistance is formed by a specific preparation method.

Benefits of technology

This coating significantly improves the anti-adhesion effect of the injection mold, extends the service life of the mold, and enhances its wear and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204832980000091
    Figure BDA0005204832980000091
Patent Text Reader

Abstract

The invention relates to an anti-adhesion coating for an injection mold and a preparation method of the anti-adhesion coating, and belongs to the technical field of high polymer materials. The anti-adhesion coating for the injection mold is prepared from the following components in parts by weight: 30 to 50 parts of polytetrafluoroethylene water-based resin, 10 to 20 parts of methyl methacrylate, 10 to 30 parts of acrylic resin, 1 to 10 parts of a modified anti-adhesion agent, 1 to 5 parts of nano silicon dioxide / graphene oxide (PDA), 0.1 to 2 parts of an auxiliary agent and 10 to 50 parts of a diluent, a fluorocarbon chain and a silicon-oxygen bond in the modified anti-adhesion agent cooperate to improve the non-stickiness, and carboxyl of 3-mercaptopropionic acid reacts with metal ions of an injection mold to enhance the adhesion; nano-silicon dioxide in the nano-silicon dioxide / graphene oxide coated PDA prolongs the path and increases the corrosion resistance, and the graphene oxide is coated with polydopamine, so that the wear resistance is improved; the prepared anti-adhesion coating for the injection mold not only has an excellent anti-adhesion effect, but also has good wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an anti-adhesion coating for an injection mold and a preparation method thereof. Background Art

[0002] Moulds are key moulds and tools used in industrial production for injection moulding, blow moulding, extrusion, die casting, forging, smelting and stamping to manufacture the required products. They are known as the "mother of industry".

[0003] In the production process of rubber products, the adhesion problem between the surface of the injection mold and the product has long plagued rubber product producers. The adhesion problem not only causes defects on the surface of the product and affects product quality, but also requires frequent mold cleaning, which reduces production efficiency, damages the mold surface and reduces the mold dimensional accuracy. In order to solve this problem, the surface of the injection mold is treated with an anti-stick coating, but traditional anti-stick coatings are easy to fall off during use and have a short lifespan. In addition, the injection mold also has poor corrosion resistance after long-term use, resulting in a decrease in overall performance. In addition, although the anti-stick coating for injection molds has a certain wear resistance, with the increase in actual application needs, its own wear resistance can no longer meet the needs. Therefore, the research and development of excellent anti-stick coatings for injection molds has important practical significance and application value. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an anti-adhesion coating for an injection mold and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An anti-adhesion coating for an injection mold and a preparation method thereof, comprising the following raw materials in parts by weight: 30-50 parts of polytetrafluoroethylene water-based resin, 10-20 parts of methyl methacrylate, 10-30 parts of acrylic resin, 1-10 parts of modified anti-adhesion agent, 1-5 parts of nano-silicon dioxide / graphene oxide @PDA, 0.1-2 parts of auxiliary agent, and 10-50 parts of diluent;

[0007] The auxiliary agent is polyether-modified polydimethylsiloxane;

[0008] The diluent is ethyl acetate.

[0009] The modified anti-adhesion agent is prepared by the following method:

[0010] Step A1: disperse nano titanium dioxide in an ethanol-water mixed solution, adjust the pH to 10, then add γ-aminopropyltriethoxysilane, 3-butylenetriethoxysilane and tetraethyl orthosilicate, stir evenly, react at 45°C for 2.5h, filter, wash, extract in a Soxhlet extractor for 20h, and dry at 80°C for 24h to obtain compound 1;

[0011] Furthermore, the dosage ratio of nano titanium dioxide, ethanol-water mixed solution, γ-aminopropyltriethoxysilane, 3-butylenetriethoxysilane, and tetraethyl orthosilicate is 5-10 g: 40-100 mL: 4-8 g: 4-5 g: 2-3 g, and the mass ratio of ethanol to water in the ethanol-water mixed solution is 2:1;

[0012] Step A2: Compound 1, 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, acetone and triethylamine were mixed uniformly, stirred at room temperature for 2-3 hours, rotary evaporated, washed and dried to obtain compound 2;

[0013] Further, the usage ratio of compound 1, 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, acetone, and triethylamine is 0.5-1.2 g: 1.85-2.53 g: 20 mL: 0.5-0.6 mL;

[0014] Step A3: 3-mercaptopropionic acid, dibutylamine and acetone were mixed evenly, magnetically stirred for 30 minutes, and then compound 2 was added and stirred evenly, reacted for 4 hours, rotary evaporated, washed, and dried to obtain a modified anti-adhesion agent;

[0015] Furthermore, the mass ratio of 3-mercaptopropionic acid, dibutylamine, acetone, and compound 2 is 4.89-5.11 g: 0.013 g: 8-10 g: 5.18-5.24 g.

[0016] The nano silicon dioxide / graphene oxide @PDA is prepared by the following method:

[0017] Step B1: nano-silica and toluene were mixed evenly, stirred in a constant temperature water bath at 80° C. for 15 min, 11-aminoundecyltrimethoxysilane was added and mixed, reacted at 80° C. for 9 h, the pH was adjusted to 5, and graphene oxide powder was added, mixed in an ultrasonic stirrer for 30 min, centrifuged, washed, and dried at 60° C. to obtain a nano-silica / graphene oxide composite;

[0018] Further, the usage ratio of nano-silicon dioxide, toluene, 11-aminoundecyltrimethoxysilane, and graphene oxide powder is 2.5-5 g: 100 mL: 1.25-5 mL: 1-2 g;

[0019] Step B2: Mix the nano-silica / graphene oxide composite with deionized water, perform ultrasonic treatment for 60 minutes, then add tris(hydroxymethyl)aminomethane hydrochloride) and dopamine hydrochloride and mix evenly, react at 60° C. for 24 hours, filter, centrifuge, wash, and vacuum dry at 60° C. for 24 hours to obtain nano-silica / graphene oxide@PDA;

[0020] Furthermore, the usage ratio of the nano-silicon dioxide / graphene oxide composite, deionized water, tris(hydroxymethyl)aminomethane hydrochloride) and dopamine hydrochloride is 0.2-1 g: 200 mL: 0.032-0.041 g: 0.4-0.5 g.

[0021] A method for preparing an anti-adhesion coating for an injection mold comprises the following steps:

[0022] S1. Preheating polytetrafluoroethylene water-based resin, methyl methacrylate and acrylic resin at a temperature of 40-60° C. for 10-20 min, adding diluent after preheating, and stirring at 800-1000 rpm for 30-40 min to obtain a pretreated material;

[0023] S2. Add the modified anti-adhesion agent, nano-silicon dioxide / graphene oxide @PDA and additives to the pretreated material, stir for 30-50 minutes, filter, and obtain the anti-adhesion coating for injection molds.

[0024] Beneficial effects of the present invention:

[0025] The flame-retardant rubber-plastic thermal insulation material of the invention has good anti-adhesion effect, and also has excellent wear resistance and corrosion resistance, thereby extending the service life of the material.

[0026] The modified anti-adhesion agent prepared by the invention comprises the following steps: firstly, silanol groups of gamma-aminopropyltriethoxysilane, 3-butylenetriethoxysilane and tetraethyl orthosilicate are hydrolyzed into silanol groups to react and form polysiloxane, and then the polysiloxane is dehydrated and condensed with hydroxyl groups on the surface of nano-titanium dioxide to synthesize compound 1 containing amino groups and carbon-carbon double bonds; secondly, the amino groups of compound 1 are reacted with chlorine atoms of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane to synthesize compound 2; and finally, the carbon-carbon double bonds of compound 2 are reacted with the mercapto groups of 3-mercaptopropionic acid to prepare the modified anti-adhesion agent. Among the modified anti-adhesion agents, fluorine is not easy to interact with other substances due to its extremely low surface energy, which effectively reduces the adhesion of the coating. The fluorocarbon chain and the silicon-oxygen bond work synergistically to give the coating excellent hydrophobicity. The fluorine atom has a small radius, a long CF bond, a large bond energy, and a strong electronegativity, which creates a strong repulsive force around the fluorine atom, causing the fluorine atom to be distributed helically along the carbon chain. In addition, the polarizability of fluorine is extremely small, and the molecular chain is non-polar and insulating, showing thermal stability and chemical inertness, resulting in the fluorocarbon-containing coating to have non-stickiness, easy cleaning, low surface tension, oil and water repellency, no pollution, and excellent self-lubricating properties after forming a coating. The coating has good slip resistance, low friction and high chemical stability; among them, nano titanium dioxide not only has excellent hydrophobicity and oleophobicity, forming a protective film on the surface of the coating to prevent liquid and solid adhesion, but also can disperse ultraviolet rays, protect the coating from damage by ultraviolet rays, extend the service life of the coating, and prevent material oxidation, enhancing the durability of the material; in addition, the carboxyl group of 3-mercaptopropionic acid can react with the metal ions of the injection mold to form a coordination bond, enhance the adhesion between the coating and the mold surface, avoid falling off during use, and solve the migration, incompatibility and volatilization problems of traditional modified anti-adhesion agents.

[0027] The nano-silicon dioxide / graphene oxide @PDA prepared by the present invention comprises the following steps: firstly, nano-silicon dioxide is reacted with a silane coupling agent 11-aminoundecyltrimethoxysilane to make its surface contain amino groups, and then the amino groups on its surface are reacted with carboxyl groups of graphene oxide to prepare a nano-silicon dioxide / graphene oxide composite; secondly, dopamine hydrochloride is self-polymerized on the surface of the nano-silicon dioxide / graphene oxide composite to generate polydopamine to synthesize the nano-silicon dioxide / graphene oxide @PDA. In nano-silica / graphene oxide @PDA, nano-silica can fill the cracks and holes generated when the resin is cured, extend the penetration path, and enhance the corrosion resistance of the coating. At the same time, it forms a three-dimensional network structure with the resin, improves the hardness of the coating, enhances the wear resistance of the coating, and extends the service life; in addition, the two-dimensional lamellar structure of graphene oxide has a large specific surface area, which effectively blocks the erosion of external substances, reduces wear and corrosion, and enhances the density and stability of the coating. Its high mechanical strength and toughness form a strong network structure in the coating, improving the overall strength and wear resistance. In addition, polydopamine itself has excellent dispersibility and is coated on the surface of graphene oxide, promoting the uniform dispersion of the nano-silica / graphene oxide composite in the resin, effectively avoiding the agglomeration and phase separation problems of nano-fillers, and strengthening the interfacial bonding between the filler and the resin matrix, thereby improving the overall wear resistance. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Embodiment 1: A method for preparing an anti-adhesion coating for an injection mold, comprising the following steps:

[0030] S1. Weigh the raw materials by weight: 30 parts of polytetrafluoroethylene water-based resin, 10 parts of methyl methacrylate, 10 parts of acrylic resin, 1 part of modified anti-adhesion agent (prepared in this embodiment), 1 part of nano-silicon dioxide / graphene oxide @PDA (prepared in this embodiment), 0.1 part of auxiliary agent, and 10 parts of diluent; preheat the polytetrafluoroethylene water-based resin, methyl methacrylate and acrylic resin at 40° C. for 10 min, add ethyl acetate after preheating, and stir at 800 rpm for 30 min to obtain a pretreated material;

[0031] S2, adding the modified anti-adhesion agent, nano-silica / graphene oxide @PDA and polyether-modified polydimethylsiloxane to the pretreated material, stirring for 30 minutes, filtering, and preparing an anti-adhesion coating for injection molds;

[0032] The modified anti-adhesion agent is prepared by the following method:

[0033] Step A1: 5 g of nano titanium dioxide was dispersed in 40 mL of an ethanol-water mixed solution, the pH was adjusted to 10, and then 4 g of γ-aminopropyltriethoxysilane, 4 g of 3-butylenetriethoxysilane and 2 g of tetraethyl orthosilicate were added, stirred evenly, reacted at 45° C. for 2.5 h, filtered, washed, put into a Soxhlet extractor for extraction for 20 h, and dried at 80° C. for 24 h to obtain compound 1, wherein the mass ratio of ethanol to water in the ethanol-water mixed solution was 2:1;

[0034] Step A2: 0.5 g of compound 1, 1.85 g of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, 20 mL of acetone and 0.5 mL of triethylamine were mixed evenly, stirred at room temperature for 2 h, rotary evaporated, washed and dried to obtain compound 2;

[0035] Step A3: 4.89 g of 3-mercaptopropionic acid, 0.013 g of dibutylamine and 8 g of acetone were mixed evenly, and magnetically stirred for 30 min, and then 5.18 g of compound 2 was added and stirred evenly, and the mixture was reacted for 4 h, and then rotary evaporated, washed and dried to obtain a modified anti-adhesion agent;

[0036] The nano silicon dioxide / graphene oxide @PDA is prepared by the following method:

[0037] Step B1: 2.5 g of nano-silica and 100 mL of toluene were mixed evenly, stirred in a constant temperature water bath at 80° C. for 15 min, and then 1.25 mL of 11-aminoundecyltrimethoxysilane was added and mixed, reacted at 80° C. for 9 h, the pH was adjusted to 5, and then 1 g of graphene oxide powder was added, mixed in an ultrasonic stirrer for 30 min, centrifuged, washed, and dried at 60° C. to obtain a nano-silica / graphene oxide composite;

[0038] Step B2: 0.2 g of nano-silica / graphene oxide composite was mixed with 200 mL of deionized water, ultrasonicated for 60 min, and then 0.03 g of tris(hydroxymethyl)aminomethane hydrochloride) and 0.4 g of dopamine hydrochloride were added and mixed evenly, reacted at 60 ° C for 24 h, filtered, centrifuged, washed, and vacuum dried at 60 ° C for 24 h to obtain nano-silica / graphene oxide @PDA.

[0039] Embodiment 2: A method for preparing an anti-adhesion coating for an injection mold, comprising the following steps:

[0040] S1. Weigh the raw materials by weight: 40 parts of polytetrafluoroethylene water-based resin, 15 parts of methyl methacrylate, 20 parts of acrylic resin, 5 parts of modified anti-adhesive agent (prepared in this embodiment), 3 parts of nano-silicon dioxide / graphene oxide @PDA (prepared in this embodiment), 1 part of auxiliary agent, and 30 parts of diluent; preheat the polytetrafluoroethylene water-based resin, methyl methacrylate and acrylic resin at a preheating temperature of 50° C. for 15 min, add ethyl acetate after preheating, and stir at 900 rpm for 35 min to obtain a pretreated material;

[0041] S2, adding the modified anti-adhesion agent, nano-silica / graphene oxide @PDA and polyether-modified polydimethylsiloxane to the pretreated material, stirring for 40 minutes, filtering, and preparing an anti-adhesion coating for injection molds;

[0042] The modified anti-adhesion agent is prepared by the following method:

[0043] Step A1: 7 g of nano titanium dioxide was dispersed in 70 mL of an ethanol-water mixed solution, the pH was adjusted to 10, and then 6 g of γ-aminopropyltriethoxysilane, 4.5 g of 3-butylenetriethoxysilane and 2.5 g of tetraethyl orthosilicate were added, stirred evenly, reacted at 45° C. for 2.5 h, filtered, washed, put into a Soxhlet extractor for extraction for 20 h, and dried at 80° C. for 24 h to obtain compound 1, wherein the mass ratio of ethanol to water in the ethanol-water mixed solution was 2:1;

[0044] Step A2: 0.85 g of compound 1, 2.19 g of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, 20 mL of acetone and 0.55 mL of triethylamine were mixed evenly, stirred at room temperature for 2.5 h, rotary evaporated, washed and dried to obtain compound 2;

[0045] Step A3: 5 g of 3-mercaptopropionic acid, 0.013 g of dibutylamine and 9 g of acetone were mixed evenly, and magnetically stirred for 30 min, and then 5.21 g of compound 2 was added and stirred evenly, and the mixture was reacted for 4 h, and then rotary evaporated, washed and dried to obtain a modified anti-adhesion agent;

[0046] The nano silicon dioxide / graphene oxide @PDA is prepared by the following method:

[0047] Step B1: 3.75 g of nano-silica and 100 mL of toluene were mixed evenly, stirred in a constant temperature water bath at 80° C. for 15 min, 3.125 mL of 11-aminoundecyltrimethoxysilane was added, reacted at 80° C. for 9 h, the pH was adjusted to 5, 1.5 g of graphene oxide powder was added, mixed in an ultrasonic stirrer for 30 min, centrifuged, washed, and dried at 60° C. to obtain a nano-silica / graphene oxide composite;

[0048] Step B2: 0.6 g of nano-silica / graphene oxide composite was mixed with 200 mL of deionized water, ultrasonicated for 60 min, and then 0.0365 g of tris(hydroxymethyl)aminomethane hydrochloride) and 0.45 g of dopamine hydrochloride were added and mixed evenly, reacted at 60 ° C for 24 h, filtered, centrifuged, washed, and vacuum dried at 60 ° C for 24 h to obtain nano-silica / graphene oxide @PDA.

[0049] Embodiment 3: A method for preparing an anti-adhesion coating for an injection mold, comprising the following steps:

[0050] S1. Weigh the raw materials by weight: 50 parts of polytetrafluoroethylene water-based resin, 20 parts of methyl methacrylate, 30 parts of acrylic resin, 10 parts of modified anti-adhesive agent (prepared in this embodiment), 5 parts of nano-silicon dioxide / graphene oxide @PDA (prepared in this embodiment), 2 parts of auxiliary agent, and 50 parts of diluent; preheat the polytetrafluoroethylene water-based resin, methyl methacrylate and acrylic resin at 60° C. for 20 min, add ethyl acetate after preheating, and stir at 1000 rpm for 40 min to obtain a pretreated material;

[0051] S2, adding the modified anti-adhesion agent, nano-silica / graphene oxide @PDA and polyether-modified polydimethylsiloxane to the pretreated material, stirring for 50 minutes, filtering, and preparing an anti-adhesion coating for injection molds;

[0052] The modified anti-adhesion agent is prepared by the following method:

[0053] Step A1: 10 g of nano titanium dioxide was dispersed in 100 mL of an ethanol-water mixed solution, the pH was adjusted to 10, and then 8 g of γ-aminopropyltriethoxysilane, 5 g of 3-butylenetriethoxysilane and 3 g of tetraethyl orthosilicate were added, stirred evenly, reacted at 45° C. for 2.5 h, filtered, washed, put into a Soxhlet extractor for extraction for 20 h, and dried at 80° C. for 24 h to obtain compound 1, wherein the mass ratio of ethanol to water in the ethanol-water mixed solution was 2:1;

[0054] Step A2: 1.2 g of compound 1, 2.53 g of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, 20 mL of acetone and 0.6 mL of triethylamine were mixed evenly, stirred at room temperature for 3 h, rotary evaporated, washed and dried to obtain compound 2;

[0055] Step A3: 5.11 g of 3-mercaptopropionic acid, 0.013 g of dibutylamine and 10 g of acetone were mixed evenly, and magnetically stirred for 30 min, and then 5.24 g of compound 2 was added and stirred evenly, and the mixture was reacted for 4 h, and then rotary evaporated, washed and dried to obtain a modified anti-adhesion agent;

[0056] The nano silicon dioxide / graphene oxide @PDA is prepared by the following method:

[0057] Step B1: 5 g of nano-silica and 100 mL of toluene were mixed evenly, stirred in a constant temperature water bath at 80° C. for 15 min, 5 mL of 11-aminoundecyltrimethoxysilane was added, and the mixture was reacted at 80° C. for 9 h, the pH was adjusted to 5, and 2 g of graphene oxide powder was added, mixed in an ultrasonic stirrer for 30 min, centrifuged, washed, and dried at 60° C. to obtain a nano-silica / graphene oxide composite;

[0058] Step B2: 1 g of nano-silica / graphene oxide composite was mixed with 200 mL of deionized water, ultrasonicated for 60 min, and then 0.041 g of tris(hydroxymethyl)aminomethane hydrochloride) and 0.5 g of dopamine hydrochloride were added and mixed evenly, reacted at 60 ° C for 24 h, filtered, centrifuged, washed, and vacuum dried at 60 ° C for 24 h to obtain nano-silica / graphene oxide @PDA.

[0059] Comparative Example 1: This comparative example is an anti-adhesion coating for injection molds. The difference from Example 3 is that an equal amount of polydimethylsiloxane is used to replace the modified anti-adhesion agent prepared in Example 3, and the rest is the same.

[0060] Comparative Example 2: This comparative example is an anti-adhesion coating for injection molds. The difference from Example 3 is that an equal amount of aluminum oxide is used instead of the nano-silicon dioxide / graphene oxide @PDA prepared in Example 3, and the rest is the same.

[0061] Performance test: The anti-adhesion coating was applied to the injection molds prepared in Examples 1-3 and the comparative example, and the coating of the mold was cut into 100 squares of 2 mm × 2 mm by a cutting machine. A transparent tape was adhered to the surface of the molds, and the molds were quickly peeled off at 90°. The number of squares left was calculated to test the apparent adhesion between the injection molds and the coating. The wear resistance was tested by a MG2000 high temperature friction and wear tester. The test environment temperature was 25°C, the load was 20N, the speed was 0.4m / s, and the sliding distance was 300m. The wear distance of the mold when it was removed from the injection molded product at a removal angle of 0-20° was tested, and the number of injections was 150 times. The salt spray resistance time test was also performed. The test results are shown in the following table:

[0062] Table 1

[0063]

[0064] It can be seen from the test data in Table 1 that the anti-adhesion coating for injection molds prepared in the present invention has excellent corrosion resistance. It can also be seen from the above table that the anti-adhesion coating for injection molds prepared in the present invention has good wear resistance and anti-adhesion effect.

[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-adhesion coating for an injection mold, characterized in that: The specific steps include: S1. Weigh the raw materials by weight: 30-50 parts of polytetrafluoroethylene water-based resin, 10-20 parts of methyl methacrylate, 10-30 parts of acrylic resin, 1-10 parts of modified anti-adhesion agent, 1-5 parts of nano-silicon dioxide / graphene oxide @PDA, 0.1-2 parts of auxiliary agent, and 10-50 parts of diluent; preheat the polytetrafluoroethylene water-based resin, methyl methacrylate and acrylic resin at a preheating temperature of 40-60° C. for 10-20 min, add the diluent after preheating, and stir at 800-1000 rpm for 30-40 min to obtain a pretreated material; S2. Add the modified anti-adhesion agent, nano-silicon dioxide / graphene oxide @PDA and additives to the pretreated material, stir for 30-50 minutes, filter, and obtain the anti-adhesion coating for injection molds.

2. The method for preparing an anti-adhesion coating for injection mold according to claim 1, characterized in that: The modified anti-adhesion agent is prepared by the following method: Step A1: disperse nano titanium dioxide in an ethanol-water mixed solution, adjust the pH to 10, then add γ-aminopropyltriethoxysilane, 3-butylenetriethoxysilane and tetraethyl orthosilicate, stir evenly, react at 45°C for 2.5h, filter, wash, extract in a Soxhlet extractor for 20h, and dry at 80°C for 24h to obtain compound 1; Step A2: Compound 1, 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, acetone and triethylamine were mixed uniformly, stirred at room temperature for 2-3 hours, rotary evaporated, washed and dried to obtain compound 2; Step A3: 3-mercaptopropionic acid, dibutylamine and acetone were mixed evenly, magnetically stirred for 30 minutes, and then compound 2 was added and stirred evenly. The mixture was reacted for 4 hours, and then rotary evaporated, washed and dried to obtain a modified anti-adhesion agent.

3. The method for preparing an anti-adhesion coating for injection mold according to claim 2, characterized in that: In step A1, the usage ratio of nano titanium dioxide, ethanol-water mixed solution, γ-aminopropyltriethoxysilane, 3-butylenetriethoxysilane, and tetraethyl orthosilicate is 5-10g:40-100mL:4-8g:4-5g:2-3g, and the mass ratio of ethanol to water in the ethanol-water mixed solution is 2:

1.

4. The method for preparing an anti-adhesion coating for injection mold according to claim 2, characterized in that: In step A2, the usage ratio of compound 1, 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, acetone and triethylamine is 0.5-1.2 g: 1.85-2.53 g: 20 mL: 0.5-0.6 mL.

5. The method for preparing an anti-adhesion coating for injection mold according to claim 2, characterized in that: In step A3, the mass ratio of 3-mercaptopropionic acid, dibutylamine, acetone and compound 2 is 4.89-5.11 g: 0.013 g: 8-10 g: 5.18-5.24 g.

6. The method for preparing an anti-adhesion coating for injection mold according to claim 1, characterized in that: The nano silicon dioxide / graphene oxide @PDA is prepared by the following method: Step B1: nano-silica and toluene were mixed evenly, stirred in a constant temperature water bath at 80° C. for 15 min, 11-aminoundecyltrimethoxysilane was added and mixed, reacted at 80° C. for 9 h, the pH was adjusted to 5, and graphene oxide powder was added, mixed in an ultrasonic stirrer for 30 min, centrifuged, washed, and dried at 60° C. to obtain a nano-silica / graphene oxide composite; Step B2: The nano-silica / graphene oxide composite was mixed with deionized water, ultrasonicated for 60 min, and then tris(hydroxymethyl)aminomethane hydrochloride) and dopamine hydrochloride were added and mixed evenly, reacted at 60° C. for 24 h, filtered, centrifuged, washed, and vacuum dried at 60° C. for 24 h to obtain nano-silica / graphene oxide@PDA.

7. The method for preparing an anti-adhesion coating for injection mold according to claim 6, characterized in that: In step B1, the usage ratio of nano-silica, toluene, 11-aminoundecyltrimethoxysilane, and graphene oxide powder is 2.5-5 g: 100 mL: 1.25-5 mL: 1-2 g.

8. The method for preparing an anti-adhesion coating for injection mold according to claim 6, characterized in that: In step B2, the usage ratio of the nano-silicon dioxide / graphene oxide composite, deionized water, tris(hydroxymethyl)aminomethane hydrochloride) and dopamine hydrochloride is 0.2-1 g: 200 mL: 0.032-0.041 g: 0.4-0.5 g.

9. The method for preparing an anti-adhesion coating for injection mold according to claim 1, characterized in that: The auxiliary agent is polyether modified polydimethylsiloxane and the diluent is ethyl acetate.

10. An anti-adhesion coating for injection molds, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Modified graphene oxide anticorrosive coating and preparation method thereof

    CN113292902A

  • Preparation method and application of modified hydroxypropyl silicone oil

    CN114763437A

  • Anticorrosive wear-resistant non-stick pan coating and preparation method thereof

    CN118580751A

  • Electrolyte system

    WO2024201348A1